Digitized Diaries - Hunter, David (The Diary Index, 2015)
This list of open access, digitized diaries is designed to assist students and scholars interested in studying diaries.
Keywords: _open access

The Noise-Arch Archive (2011)
This collection is a compilation of underground/independently-released cassette tapes from the days when the audio cassette was the standard method of music sharing... generally the mid-eighties through early-nineties. The material represented includes tape experimentation, industrial, avant-garde, indy, rock, diy, subvertainment and auto-hypnotic materials. Much of this material defies category, and has therefore not been given one. The bulk of the tapes in this library were donated to the project by former CKLN FM radio host Myke Dyer in August of 2009. The original NOISE-ARCH site was hosted and maintained by Graham Stewart and Mark Lougheed.
Keywords: _open access

The Maryland Motherlode: Births, Marriages, Deaths, and Naturalizations (Reclaim The Records)
Keywords: _open access

New Deal (National Archives, 2016)
Links to web sites relating to the New Deal era useful for research on New Deal agriculture, labor, and arts programs. The New Deal , Painting/Mural by Conrad A. Albrizio. Dedicated to President Roosevelt. Placed in the auditorium of the Leonardo Da Vinci Art School, 149 East 34th Street, New York, New York,& ca. 1934 (FDR Presidential Library NLR-PHOCO-A-59333) Contents NARA Resources Other Resources NARA Resources "Archival Vintages for The Grapes of Wrath" Daniel Nealand's Prologue article shows how John Steinbeck used WPA documentary source material provided by Thomas E.
Keywords: _open access

Herbert Hoover Papers - Anonymous (The Herbert Hoover Presidential Library and Museum, 2017)
The papers of Herbert Hoover had been accumulating since 1919 at the Hoover Institution on War, Revolution, and Peace at Stanford University. In 1960 Hoover decided to donate materials beginning with his time as Secretary of Commerce onwards to the Herbert Hoover Presidential Library. The papers are arranged into five groups. Hoover Papers [accordion classes="" id="903" expand_first="false"][/accordion]
Keywords: _open access

UW-Madison Libraries Collections
Keywords: _open access

American Baptist Historical Society (American Baptist Historical Society, 2023)
The American Baptist Historical Society (ABHS) holds the archives and serves as the historical interpreter of a major religious denomination — American Baptist Churches USA — made up of 4,900 churches and 1.2 million people. ABHS archival collections include records from many different Baptist organizations in North America and around the world. As the oldest Baptist historical society (founded in 1853) with the largest and most diverse collection of Baptist historical material, our holdings are of irreplaceable value to church, national, and global history. ABHS serves as keeper of the record of the modern missionary movement. Our shelves hold unparalleled resources documenting African-American church associations, women’s work, local church and association minutes, and the social gospel movement. We publish the oldest Baptist journal, Foundations, interpreting for modern readers the lives and issues of the past that shape who we are today.
Keywords: _open access

Houston Mutiny and Riot Records (South Texas College of Law Houston Digital Collections)
Keywords: _open access

Women Working, 1800-1930 (CURIOSity Digital Collections)
An exploration of women's impact on the economic life of the United States between 1800 and the Great Depression.
Keywords: _open access

Eugenics Archive
Keywords: _open access

Chronicling America - National Endowment for the Humanities (Library of Congress)
Search America's historic newspaper pages from 1770-1963 or use the U.S. Newspaper Directory to find information about American newspapers published between 1690-present.
Keywords: _open access